Long Non-Coding RNA MAPK8IP1P2 Inhibits Lymphatic Metastasis of Thyroid Cancer by Activating Hippo Signaling via Sponging miR-146b-3p - Liu, Xiaoli; Fu, Qingfeng; Bian, Xuehai; Fu, Yantao; Xin, Jingwei; Liang, Nan; Li, Shijie; Zhao, Yishen; Fang, Li; Li, Changlin; Zhang, Jiao; Dionigi, Gianlorenzo; et al. (Frontiers in Oncology, 2021)
The principal issue derived from thyroid cancer is its high propensity to metastasize to lymph node. Aberrant exprssion of long non-coding RNAs have been extensively reported to be significantly correlated with lymphatic metastasis of thyroid cancer. However, the clinical significance and functional role of lncRNA-MAPK8IP1P2 in lymphatic metastasis of thyroid cancer remain unclear. Here, we reported that MAPK8IP1P2 was downregulated in thyroid cancer tissues with lymphatic metastasis. Upregulating MAPK8IP1P2 inhibited, while silencing MAPK8IP1P2 enhanced anoikis resistance in vitro and lymphatic metastasis of thyroid cancer cells in vivo. Mechanistically, MAPK8IP1P2 activated Hippo signaling by sponging miR-146b-3p to disrupt the inhibitory effect of miR-146b-3p on NF2, RASSF1 and RASSF5 expression, which further inhibited anoikis resistance and lymphatic metastasis in thyroid cancer. Importantly, miR-146b-3p mimics reversed the inhibitory effect of MAPK8IP1P2 overexpression on anoikis resistance of thyroid cancer cells. In conclusion, our findings suggest that MAPK8IP1P2 may serve as a potential biomarker to predict lymphatic metastasis in thyroid cancer, or a potential therapeutic target in lymphatic metastatic thyroid cancer.